Progress towards a methodology for high throughput 3D reconstruction of soot nanoparticles via electron tomography - Haffner-Staton, Ephraim; La Rocca, Antonino; Fay, Mike W. (Wiley, 2018)
The aim of this work is to make progress towards the development of 3D reconstruction as a legitimate alternative to traditional 2D characterisation of soot. Time constraints are the greatest opposition to its implementation, as currently reconstruction of a single soot particle takes around 5-6 hours to complete. As such, the accuracy and detail gains are currently insufficient to challenge 2D characterisation of a representative sample (e.g. 200 particles). This work is a consideration of the optimisation of the steps included within the computational reconstruction and manual segmentation of soot particles. Our optimal process reduced the time required by over 70% in comparison to a typical procedure, whilst producing models with no appreciable decrease in quality.